2016
DOI: 10.1111/aor.12733
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Index Declines During Long‐Term Left Ventricular Device Support

Abstract: To investigate longitudinal trends in valvular and ventricular function with long-term left ventricular assist device (LVAD) therapy, we analyzed hemodynamic and echocardiographic data of patients with at least 2 years of continuous LVAD support. All 130 patients who underwent HeartMate II implantation at our institution between 2005 and 2012 were reviewed. Twenty patients had hemodynamic and echocardiographic evaluations in both the early (0-6 months) and late (2-3 years) postoperative period. Patients on ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…18 The smaller study also excluded patients on inotropes, and was limited to a single device (HeartMate II). 19 In contrast, our study did not exclude these patients, in order to reduce selection bias and provide a more comprehensive view of the clinical course following LVAD. These differences in study population may explain the difference in hemodynamic trends.…”
Section: Hemodynamics After Lvad Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The smaller study also excluded patients on inotropes, and was limited to a single device (HeartMate II). 19 In contrast, our study did not exclude these patients, in order to reduce selection bias and provide a more comprehensive view of the clinical course following LVAD. These differences in study population may explain the difference in hemodynamic trends.…”
Section: Hemodynamics After Lvad Implantationmentioning
confidence: 99%
“…Our findings regarding longitudinal hemodynamic trends in LVAD patients are different from two previous studies that found an overall improvement in RV parameters during longterm follow-up. 18,19 It is important to note that the larger of these two studies excluded patients on inotropes or pulmonary vasodilators by design, in order to examine RV load independent of medications that might impact the physiology. 18 The smaller study also excluded patients on inotropes, and was limited to a single device (HeartMate II).…”
Section: Hemodynamics After Lvad Implantationmentioning
confidence: 99%
“…There are few studies reporting long-term trends in hemodynamics during LVAD support. Kalathiya et al showed in a longitudinal study that CI declined in patients with HeartMate II after 2 years of continuous support, possibly due to an increase in afterload [36]. …”
Section: Hemodynamics During Lvad Therapymentioning
confidence: 99%